2019
DOI: 10.1007/s12325-019-00998-3
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Non-Medical Switching from Originator Biologics to Biosimilars: A Systematic Literature Review

Abstract: IntroductionA systematic literature review was conducted to review and summarize the economic impact of non-medical switching (NMS) from biologic originators to their biosimilars (i.e., switching a patient’s medication for reasons irrelevant to the patient’s health).MethodsEnglish publications reporting healthcare resource utilization (HRU) or costs associated with biosimilar NMS were searched in PubMed and EMBASE over the past 10 years and from selected scientific conferences over the past 3 years, along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…Furthermore, there was no clinically meaningful difference in the proportion of ADA-positive patients between groups; the proportion of neutralizing antibody-positive patients was also similar [34]. However, data regarding the economic impact and healthcare resource use of nonmedical switching are limited, as highlighted in a recent systematic literature review that identified few studies using real-world estimations and methodological shortcomings in others [161]. Any increase in direct financial or healthcare professional (HCP) time costs related to switching patients could present an obstacle to biosimilar uptake.…”
Section: Pharmacoeconomists' Perspective: Cost Of and Access To Biolomentioning
confidence: 97%
“…Furthermore, there was no clinically meaningful difference in the proportion of ADA-positive patients between groups; the proportion of neutralizing antibody-positive patients was also similar [34]. However, data regarding the economic impact and healthcare resource use of nonmedical switching are limited, as highlighted in a recent systematic literature review that identified few studies using real-world estimations and methodological shortcomings in others [161]. Any increase in direct financial or healthcare professional (HCP) time costs related to switching patients could present an obstacle to biosimilar uptake.…”
Section: Pharmacoeconomists' Perspective: Cost Of and Access To Biolomentioning
confidence: 97%
“…33 Indeed, higher healthcare resource utilization and costs have been reported in studies of realworld switches from originator biologics to biosimilars. 27,34 In contrast to the previously mentioned studies showing negative effects associated with switching, other, non-US studies have demonstrated well-tolerated switching to IFX biosimilars and limited effects on long-term clinical outcomes. [35][36][37] Given the diverse evidence regarding biologic treatment switching in the literature, further research is warranted to examine the reasons for treatment switching and discontinuations using real-world data.…”
Section: Discussionmentioning
confidence: 99%
“…when a patient is switched from a reference biologic to its biosimilar, is switched back, or is switched between biosimilars out of an, for example, economic rationale [40]. Whether non-medical switching from reference biologics to biosimilars is associated with costs is not (yet) clear: a recent systematic literature review found limited evidence on this topic and pointed to methodological limitations of existing studies [41]. Nevertheless, NHS Scotland, for example, recommends to implement 'invest to save' arrangements to pay for managed switching programs now with a view to generate savings from biosimilar competition later [42].…”
Section: Article Highlightsmentioning
confidence: 99%